ISLAMIC COMMUNICATION ETHICS AND INDONESIAN MEDIA LAW: MITIGATING GEOPOLITICAL NARRATIVE WARFARE IN THE AGE OF GLOBAL INFORMATION DISORDER - Amar Ahmad; Nurhidaya; Najmah Jaman (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines the dynamics of communication conflict and the fragmentation of public discourse arising from escalating geopolitical tensions involving Iran, the United States, and Israel. It addresses a gap in existing scholarship by analyzing how intense media exposure generates communicative dissonance and semantic ambiguity between grassroots narratives and formal institutional discourse. The study positions Islamic communication ethics particularly ṣidq, amānah, tablīgh, ‘adl, and the Qur’anic principle of tabayyun as the normative framework for interpreting contemporary information disorder. This research employs a qualitative analytical approach using a multi-layered communication conflict framework. It examines the interaction between digital media saturation and sociopolitical dialectics by analyzing how information flows are produced, contested, and interpreted across different communicative domains. Islamic communication ethics serve as the principal analytical lens for assessing the normative implications of media circulation and public meaning-making. The findings indicate that high-intensity media exposure intensifies the polarization of public opinion and produces structural ruptures in meaning-making. Informal public discourse frequently diverges from official institutional narratives, thereby reinforcing chronic information fragmentation and systemic communication conflict. From the perspective of Islamic communication ethics, the erosion of tabayyun weakens information integrity and accelerates the circulation of emotionally charged and unverified narratives during geopolitical crises. This study contributes to Islamic media and communication studies by demonstrating the relevance of Islamic ethical principles for understanding misinformation, discourse fragmentation, and conflict communication in the digital era. However, the research is limited by its qualitative and interpretive scope, which may not fully capture empirical variations across different sociopolitical contexts. This study proposes that contemporary geopolitical crises can be understood as localized communicative conflicts shaped by media saturation and normative disruption. By integrating Islamic communication ethics and tabayyun into debates on global information integrity, it offers a theoretical bridge between Islamic studies and contemporary media discourse.